The complex role of autophagy in glioblastoma: knocking out different types of autophagy and its implications in chemotherapy outcomes - Tomaz, Marina Andrade [UNIFESP] (2022)
The term “autophagy” refers to three distinct mechanisms: macroautophagy, chaperone mediated autophagy (CMA) and microautophagy, with macroautophagy and CMA being the most relevant types to cancer biology. Autophagy activation is associated with several cellular defense pathways, such as detoxification and DNA damage response. To better understand how distinct autophagy mechanisms impact chemoresistance, we generated LAMP2A KO and ATG7 KO glioblastoma cell lines, deficient in CMA and macroautophagy, respectively. We observed that LAMP2A KO cells presented a deficiency of antioxidant defenses. Accordingly, the loss of CMA sensitized the GBM cells for treatment with TMZ and other drugs. In contrast, ATG7 KO cells presented evidence of increased antioxidant defense and increased viability when treated with TMZ and other drugs. In cancer cells, accumulation of p62 is a way of activate NRF2, a transcription factor involved in antioxidant defenses and a classical hallmark of chemoresistance in several types of high aggressive tumors. Interestingly, ATG7 KO cell lines displayed higher levels of p62, concomitant with an increase in NRF2 compared to wild type cells, and NRF2 silencing reverted the resistant phenotype in ATG7 KO cells. Curiously, both LAMP2A and ATG7 KO models were more sensitive to proteasome inhibitors, suggesting that proteasome activity may be compensating for the lack of either autophagy. Altogether, our results contributed to demonstrate the role of different autophagy pathways in chemoresistance, as well as the complex dynamics through which tumors can overcome the loss of major cell biology pathways. Here we showed the importance of approaching these two autophagy pathways separately in order to obtain more solid responses in cancer chemoresistance mechanisms, and lead to more effective treatment protocols of glioblastoma.